Sustainable Development in Central Sulawesi: A Quadrant Approach and Variables that Shape Sustainability - Yohan, Yohan; Tallesang, Mukhtar; Rafika, Ika; Suirlan, Rita; Sindika Sari, Nurfadila; Christiani , Indah; Mustika; Nurnaningsih, Nurnaningsih (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
Sustainable development in Central Sulawesi is demonstrated by long-term disparities between regions, which highlight the imbalance between economic, social, and environmental aspects. This study set out to examine the regional sustainability performance and explain the underlying structural factors that contribute to the existing disparities. This study uses secondary data from 2021 to 2024 to create a Sustainable Development Index (SDI) and combines it with quadrant analysis to identify patterns of regional sustainability. It also uses data regression panels to test the main economic, social, and environmental determinants. The research results show that no regency or city has achieved a completely balanced sustainability position, with areas spread across the quadrants of underutilization, overexploitation, and ecological emergency. The econometric results show that human development, unemployment dynamics, and environmental quality excert a profound impact on sustainability, while economic growth and per capita GDP do not have a significant effect. Model fixed effects confirm there is strong structural heterogeneity across regions, highlighting the importance of spatial and institutional context. This study contributes to theory by improving the understanding of sustainable development and regional development, and it shows that regional sustainability inequality is formed in a structural way and cannot be explained just by growth-based indicators.